2009
DOI: 10.1093/bja/aen325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-dose ketamine on inflammatory response in off-pump coronary artery bypass graft surgery

Abstract: Background. Off-pump coronary artery bypass graft surgery (OPCAB) is still associated with a marked systemic inflammatory response. The aim of this study was to investigate whether pre-emptive, low dose of ketamine, which has been reported to have anti-inflammatory activity in on-pump coronary artery bypass surgery, could reduce inflammatory response in low-risk patients undergoing OPCAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…[79][80][81] The use of ketamine in cardiac surgery was associated with decreased inflammation, opioid sparing, and improved patient satisfaction postoperatively. [82][83][84][85][86][87][88][89][90] Its use in the prevention of chronic poststernotomy pain has not been studied.…”
Section: Acetaminophenmentioning
confidence: 99%
“…[79][80][81] The use of ketamine in cardiac surgery was associated with decreased inflammation, opioid sparing, and improved patient satisfaction postoperatively. [82][83][84][85][86][87][88][89][90] Its use in the prevention of chronic poststernotomy pain has not been studied.…”
Section: Acetaminophenmentioning
confidence: 99%
“…In another randomized, placebo-controlled trial with two doses of ketamine (0.25 or 0.5 mg/kg) vs. placebo in on-pump CABG patients during general anesthesia cardiac induction, both ketamine doses suppressed the elaboration of several pro-inflammatory markers/cytokines—C-reactive protein (CRP), IL-6, and IL-10 (but not IL-8)—with concomitant sympathomimetic effects (Bartoc et al 2006). Yes, in off-pump CABG, ketamine did not decrease serum levels of pro-inflammatory cytokines—CRP, IL-6, tumor necrosis factor-alpha (TNFα), and cardiac enzymes—in the perioperative period (Cho et al 2009). To date, there have not been any studies examining levels of pro-inflammatory mediators in response to subanesthetic-dose ketamine for major depression, but this is an area of active investigation by many groups studying ketamine as a rapidly acting anti-depressant in both the preclinical and clinical realms.…”
Section: Ketamine and Inflammationmentioning
confidence: 99%
“…Though corticosteroids have been shown to reduce the serum inflammatory markers, [20,21] neither systemic nor inhaled corticosteroids have been shown to offer clinical benefits measured in terms of pulmonary dysfunction, oxygenation, duration of mechanical ventilation, hemodynamic benefit, or improvement in pain control in patients undergoing CPB. [5,22,23] In addition, Cho et al, have studied 50 patients undergoing off-pump CABG and concluded that administration of 0.5 mg/kg of ketamine at induction of general anesthesia did not result in significant changes in serum levels of CRP, IL 6, TNF alpha and cardiac enzymes [24] even though off-pump CABG has been shown to induce marked and similar inflammatory response as that of CPB. [18,25] Ketamine has been shown not to decrease the IL-6 levels in the tracheobronchial aspirate of infants undergoing cardiac surgery.…”
Section: Resultsmentioning
confidence: 99%